HUBUNGAN PENERAPAN KOMUNIKASI SBAR DENGAN BUDAYA KESELAMATAN PASIEN PADA ERA PANDEMI COVID-19 DI RUANG RAWAT INAP RSUD PASAR MINGGU JAKARTA - Defina Ramandhani, (2021)
SBAR communication is a procedure for sending the patient's health condition as one of the factors that influence patient safety culture. The effectively application of SBAR communication in the era of Covid-19 pandemic can prevent patient safety incidents from occurring in hospitals. This study aims to identify the relationship between the application of SBAR communication with patient safety culture in the era of Covid-19 pandemic in the inpatient room of Pasar Minggu Hospital, Jakarta. This research is using descriptive analytic research design withapproach cross sectional. The technique is purposive sampling with sampling of 111 nurses. The results of the study using the Chi-Square test showed that there was a significant relationship between education and patient safety culture with p value= 0.005 (p Value <0.05) and there was a significant relationship between the application of SBAR communication and patient safety culture with p value= 0.003 (p Value<0.05). The conclusion of this study is that the application of SBAR communication has an effect on patient safety culture. Nurses are expected to be able to attend training related to patient safety and always apply SBAR communication effectively according to Standard Operating Procedures in hospitals.